2016
DOI: 10.1042/bsr20160277
|View full text |Cite
|
Sign up to set email alerts
|

Defining the extreme substrate specificity of Euonymus alatus diacylglycerol acetyltransferase, an unusual membrane-bound O-acyltransferase

Abstract: The membrane-bound O-acyltransferase Euonymus alatus diacylglycerol acetyltransferase (EaDAcT) preferentially uses acetyl-CoA to acetylate sn-1,2 DAGs but other acyl-donor and acyl-acceptor substrates can be used with low efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…Together, these results demonstrated that EaDAcT was able to acetylate MCFA diacylglycerols (DAGs) such as 1,2-dilaurin- sn -3-glycerol and 1,2-dimyristoyl- sn -3-glycerol to generate acetyl-dilaurin and acetyl-dimyristin in camelina seed. Such activities have been shown in vitro in our previous work ( Bansal and Durrett, 2016 a ).…”
Section: Resultssupporting
confidence: 76%
“…Together, these results demonstrated that EaDAcT was able to acetylate MCFA diacylglycerols (DAGs) such as 1,2-dilaurin- sn -3-glycerol and 1,2-dimyristoyl- sn -3-glycerol to generate acetyl-dilaurin and acetyl-dimyristin in camelina seed. Such activities have been shown in vitro in our previous work ( Bansal and Durrett, 2016 a ).…”
Section: Resultssupporting
confidence: 76%
“…Instead, in Brassica napus DGAT1 this hydrophilic region has been shown to interact with long-chain acyl-CoA in a positive cooperative fashion (Weselake et al, 2006). The absence of this region therefore might explain why EaDAcT possesses a non-cooperative response to acetyl-CoA concentration (Bansal and Durrett, 2016a), whereas DGAT1 enzymes possess a positive cooperative response to oleyl-CoA (Roesler et al, 2016), though additional quantification of EaDAcT activity at lower concentrations of acetyl-CoA is needed to confirm the enzyme's non-cooperative kinetics.…”
Section: Membrane Localization and Orientation Of Eadactmentioning
confidence: 99%
“…The presence of an acetyl group instead of a longer fatty acyl group gives acetyl-TAG altered physical properties compared with regular triacylglycerols (here referred to as lcTAG), including reduced viscosity and lower melting temperatures (Durrett et al, 2010;Liu et al, 2015). The preferred substrate of EaDAcT is DAG, but it is also capable of acetylating fatty alcohols to form alkyl acetates, albeit with reduced efficiency (Bansal and Durrett, 2016a;Ding et al, 2016). This weak wax synthase activity is consistent with the enzyme's sequence similarity to the jojoba wax synthase, which distances EaDAcT from the DGAT1 enzymes with which it shares a common DAG substrate (Durrett et al, 2010;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a few publications dedicated to the investigation of Ac DAG, the following synonyms can be encountered: acetylated triacylglycerols (acTAG; Bansal & Durrett, ; Durrett et al, ), 1,2‐diacyl‐3‐acetates (Kleiman et al, ), α‐acetotriglycerides (Spitzer & Aichholz, ), and monoacetyldiglycerides (MADG) (Limb, Kim, Han, & Jhon, ; Yang et al, ), of which only one unambiguously indicates the sn ‐position in the Ac DAG molecule acylated by the acetic acid residue. In the glycerol framework of Ac DAG, only one sn ‐position is acetylated—the terminal one (or, α‐position); and, therefore, logically, natural Ac DAG should be a racemic mixture of sn ‐1,2(2,3)‐diacyl‐3(1)‐acetylglycerols (Fig.…”
Section: Introductionmentioning
confidence: 99%